Pengaruh Kualitas Audit Dan Tata Kelola Perusahaan Terhadap Kecurangan Laporan Keuangan - Wahfiuddin, Muhammad; Subekti, Imam (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to obtain an empirical evidence of the effect of audit quality and corporate governance—including managerial ownership, institutional ownership, qualifications of independent commissioners, recommendations of the board of commissioners and the number of board of commissioners' meetings—on financial statement fraud. The population of this study include manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2017 and 2020, from which the samples of 52 companies with 183 total data, are selected by purposive sampling method. The multiple regression analysis results exhibit that the managerial ownership encourages financial statement fraud while corporate governance including the qualifications of independent commissioners can prevent financial statement fraud.